The Effect of Interactive Wordwall Media on Improving Elementary School Students' Mathematical Numeracy Skills - Fatmawati; Wahid Hasim (JTMT: Journal Tadris Matematika, 2026)
This study aimed to analyze the effect of interactive Wordwall media on improving elementary school students’ mathematical numeracy skills. The research employed a quantitative approach using a pre-experimental one-group pretest–posttest design. The participants were 20 third-grade students at SDN 02 Jatisari, consisting of 11 female students and 9 male students. Data were collected through a numeracy test consisting of five essay questions on multiplication material. The instrument was validated using the Product Moment correlation test and demonstrated acceptable reliability with a Cronbach’s Alpha coefficient of 0.656. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, N-Gain analysis, effect size analysis, and the Paired Sample t-test with the assistance of SPSS version 25. The results showed that students’ mean numeracy score increased from 58.40 on the pretest to 83.15 on the posttest. The N-Gain score was 0.60, indicating a moderate level of improvement, while the effect size analysis yielded a Cohen’s d value of 1.91, indicating a large effect. The Paired Sample t-test also revealed a statistically significant difference between pretest and posttest scores (p < 0.05). The findings demonstrate that interactive Wordwall media is effective in improving elementary school students’ mathematical numeracy skills and can serve as an innovative digital learning tool to support engaging mathematics instruction.